The Concept of Jewelry in the Qur’an: An Analysis of the Term Hilyah - Saoban Syahril; Muhammad Yusuf; Muhammad Irham (Madani: Jurnal Ilmiah Multidisiplin, 2026)
The purpose of this study is to explain the concept of jewelry in the Qur’an as reflected in the term ?ilyah. This research is qualitative in nature and employs a thematic analysis method. The author specifically adopts an approach from Qur’anic exegesis (tafsir) that is directly related to textual interpretation and aims to uncover textual meaning by examining each detail of the interpretive process. The results of this study indicate that, in general, jewelry in the Qur’an as denoted by the term ?ilyah refers to adornments in the form of clothing or items worn by humans to appear beautiful and attractive, usually made of gold and silver. Jewelry in the Qur’an associated with the term ?ilyah also represents various human attitudes, such as love of worldly life to the extent of idolizing it, covering the awrah (parts of the body that should be concealed), and expressing gratitude. This research is important to obtain Qur’anic guidance regarding ?ilyah as a form of adornment.